Competencies in Higher Education: a Biopolitical Strategy and a Mode of Refining of the Performative Character of Knowledge (2011)
Among the set of changes promoted in education, one which has been central to official policy is that of promoting, putting pressure on, and “attracting” educational institutions and their actors to focus on training and assessment based on competencies. The problematic context under which this policy is employed is that of a liberal government strategy updated through a neo-liberal government, which using Foucaultian terminology will be referred to in this article as government of individualization. Regarding this emphasis on competencies, the present study highlights the performative character of knowledge, and the implications that it has on learning processes, particularly in higher education.